Pengaruh Daya Ledak Otot Lengan Daya Ledak Otot Tungkai Dan Koordinasi Mata-Kaki Terhadap Ketepatan Smash Bolavoli Siswa Putra SMKN 2 Pariaman - Nanda Saputra; Ishak Aziz; Syafruddin Syafruddin; Nugroho Susanto; Damrah Damrah (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The problem in this study was the low accuracy of the smash in the men's volleyball athletes from the Genesa Ringan Ringan Club. This type of the research was quantitative research with a causal associative correlation approach. The aim of the research was to determine the effect of direct, indirect and simultaneous arm muscle explosive power, leg muscle explosive power, eye-foot coordination on the accuracy of volleyball smashes. The research sample was the men's volleyball athlete in the Ganesa Ringan Ringan Club, totaling 26 people. The sampling technique used a saturated sample, which totaled 26 male athletes. Data was collected using a test to measure the explosive power of the arm muscles, leg muscle explosive power, eye-foot coordination, and the accuracy of the volleyball smash. Data analysis technique was path analysis. The results of data analysis show that; (1) there was a significant direct effect of the explosive power of the arm muscles on the accuracy of the volleyball smash with a value of 5.07%. (2) there was a significant direct effect of the explosive power of the leg muscles on the accuracy of the volleyball smash with a value of 0.94%. (3) there was a significant direct effect of eye-hand coordination on the accuracy of the volleyball smash with a value of 0.83%. (4) there was an indirect effect of the explosive power of the arm muscles on the accuracy of the volleyball smash through eye-hand coordination with a value of 4.20%. (5) there was an indirect effect of the explosive power of the leg muscles on the accuracy of the volleyball smash through eye-hand coordination with a value of 1.88%.